A NEWCOMER TO THE POLES: EXAMINING TURKISH FOREIGN POLICY AT THE GLOBAL LEVEL - Dal, Adnan (My University, 2022)
This paper examines at what level Turkish foreign policy of late years is being implemented. It aims to delineate that contrary to the regional level policy in the first decade of the 2000s, a differentiated foreign policy is being pursued at the global level aiming to increase Turkish marine research activities at the two poles. Getting involved in science diplomacy in recent years, Turkey plans to strengthen its power capacity and evaluate it at the global level. Thus, in this paper, it is concluded that Turkey’s involvement in both the Arctic and Antarctic signifies that its foreign policy target is no more limited to regional dynamics. Significant paces in the two poles could be best understood via its foreign policy at the global level. Moreover, Turkey’s involvement in science diplomacy in parallel with polar engagement strengthens its power capacity on behalf of the global level. Consequently, it is asserted that Turkish foreign policy has been in transition from regional to global standards.
Keywords: Science Diplomacy; marine research; The Arctic; The Antarctic; Turkish foreign policy